New Irish Short Stories - O'Connor, Joseph (London Faber and Faber Publishers, 2011)
Bundel verhalen van Ierse auteurs en enkele buitenlandse auteurs met Ierse roots.
Keywords: Short stories, English -- English fiction--Irish authors -- Ireland